Cold adaptation in bacteria with special focus on cellulase production and its potential application. (10th June 2020) - Gupta, Santosh K.; Kataki, Sampriti; Chatterjee, Soumya; Prasad, Rajesh K.; Datta, Sibnarayan; Vairale, Mohan G.; Sharma, Sonika; Dwivedi, Sanjai K.; Gupta, Dharmendra K.
Abstract: Cold adapted bacteria undertake array of adaptive strategies and remain active with an active temperature range of 0–40 °C and activity in the acidic to neutral pH range (pH 4.5–7.0) to withstand in extreme environmental conditions and to retain metabolic and enzymatic activities. In soil, water or food, they were reported to comprise higher population as compared to mesophilic and thermophilic population (can make up to 86% of the total population). The present work critically discusses a detailed account of different strategies of cold adaptations in bacteria at cellular (viz. regulation of cell membrane fluidity through lipidcomposition, carotenoids production, cryoprotectants) and molecular level (differential gene expression, chaperones, proline isomerisation, antifreeze proteins, proteins and enzymes), cold-active cellulases from psychrophiles, their production strategies, the factors affecting and their properties and cold-active enzyme activities for different applications with special focus on cold-active cellulases. Due to more flexibility in protein structure and related higher binding capacity with the substrates, cold enzymes have more catalytic activities (around 10 times more than amesophilic enzyme) at cold temperatures. Attempt is made to critically analyze the practical relevance and significance of these aspects to help explore future directions of research related to scope of versatile applications of cold active enzyme. Graphical abstract: Image 10899 Highlights: Different strategic adaptations of cold active bacteria are critically reviewed. Cold active bacteria are potential source of various cold active enzymes (CAE). CAE holds huge potential for different industrial applications due to several advantages. Detail account on psychrophilic cellulase is also presented along with prospective applications. Targeted and cost-effective production method of CAE is necessary to satisfy industrial need.